2012
DOI: 10.1111/j.1745-4514.2011.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT ACTIVITY OFBENINCASA HISPIDASEEDS

Abstract: Oxidative stress induced by free radicals is the main cause of many human diseases. Plant‐derived antioxidant supplements can counter oxidative damage in cells. The purposes of this study were to investigate the effects of water extracts from dried seeds of Benincasa hispida (B. hispida) on antioxidant activity and how this related to total contents of phenolics and flavonoids in vitro. The levels of phenolic and flavonoid compounds were 81.3 ± 1.4 µg gallic acid /g and 486.8 ± 4.1 µg catechin/g dry mass, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The phenolic content of the extract was determined by using FC (Folin-Ciocalteu) method [13] . Data were expressed as gallic acid equivalents (GAE) per 100 g dry mass.…”
Section: Determination Of Total Phenolic and Total Flavonoid Contentsmentioning
confidence: 99%
“…The phenolic content of the extract was determined by using FC (Folin-Ciocalteu) method [13] . Data were expressed as gallic acid equivalents (GAE) per 100 g dry mass.…”
Section: Determination Of Total Phenolic and Total Flavonoid Contentsmentioning
confidence: 99%
“…In living organisms, oxidation is a crucial biological process for energy production, which is responsible for an excessive production of reactive oxygen species (ROS) (Arunachalam, Parimelazhagan, & Saravanan, 2011). The formation of the ROS causes aging and a number of diseases including inflammation, cancer, and other degenerative diseases in the living body (Samad et al, 2013). A wide range of phytochemicals including polyphenols and flavonoids are plenty in natural products, such as flower, fruits, and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of phytochemicals including polyphenols and flavonoids are plenty in natural products, such as flower, fruits, and vegetables. Recently, many researchers have reported that the phytochemicals may afford protection against some chronic diseases, caused by oxidative stress (Debnath, Kim, & Lim, 2013;Samad et al, 2013). These phytochemicals can scavenge the free radicals by inhibiting their initiation and chain propagation.…”
Section: Introductionmentioning
confidence: 99%
“…After the run, plates are dried and the spots were detected by using the UV spectrometer. The movement of the active compound was expressed by its retention factor (RF) values were calculated for different samples 14 .…”
Section: Preparation Of Fatty Acid Methyl Estermentioning
confidence: 99%